Model tingkat kemiskinan Provinsi Jawa Timur dengan analisis regresi spasial (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
Poverty is a major problem in the developing countries, as in Indonesia. In 2008, East Java Province was one of Indonesia's richest provinces, but it also occupied third place with a high number and percentage of poor people. The poverty figures in East Java Province have been declining before, and 2008 is the lowest seen figure of both size and percentage. The poverty of an area is affected by the poverty of its surroundings. So in the analyzing data containing spatial effects or regional aspects, spatial regression was used. The best Spatial Regression Model used is the Spatial Error Model (SEM). The variable used in this study is the poverty rate in the East Java Province as variable (Y), with nine X variables: namely the head of the woman's household (X1), the number of children not in school 7-18 years (X2), the number of individuals with disabilities (X3), the number of individuals with chronic disease (X4), the number of individuals not working (X5), the unprotected drinking water sources (X6),  defecating without latrines (X7), non- electrical lighting (X8), the fuel cook using oil and wood (X9). The weighting matrix used is the Queen Contiguity Matrix. The results of the modeling using SEM and the factors that affect poverty are the number of individuals with disabilities (X3) and the unprotected drinking water sources (X6).
Keywords: proverty; spatial regression; spatial error model